Community-Based Cultural Tourism Potential In Karangturi Tourism Village, Lasem District, Rembang Regency - Sofiani Sofiani; Kevin Gustian Yulius; Gracia Eugene Hardjasa (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
Karangturi Tourism, Lasem District, Rembang Regency, which is famous for its acculturation of Javanese and Chinese cultures, as well as the heritage of Lasem batik which is a symbol of local cultural identity. Lasem, known as "Little China" in Central Java, has rich historical and cultural values, where Lasem batik, with its distinctive motifs and colors, is the main tourist attraction. Although Karangturi Village has basic infrastructure such as hotels, hostels, and food stalls, the management of community-based tourism (CBT) is still not optimal. Limitations in local tourism management, promotion, and cultural preservation are challenges in developing this village as a culture-based tourism destination. This study aims to explore the potential of community-based cultural tourism in Karangturi Village and strategies that can increase active community participation in tourism management, with a focus on the integration of Lasem batik in the development of community-based tourism. This research will be conducted in Karangturi Village by involving various stakeholders, such as local communities, batik craftsmen, tourism business managers, and local government. Data were collected through Focus Group Discussions (FGD), semi-structured interviews, and field observations. The data obtained will be analyzed using thematic analysis, SWOT matrix. The results of the study show that Karangturi Lasem Tourism Village has a very strong cultural identity, especially in history, typical Chinese architecture, and unique Lasem batik. The existence of supporting facilities also provides added value for tourist comfort. However, challenges such as less than optimal transportation access and less than optimal promotion are obstacles that need to be overcome. Opportunities from the growing trend of cultural tourism and government support can be utilized with more aggressive and innovative marketing strategies. The contribution of this research is to make improvements in several sectors that are still less than optimal.